Penerapan Model Problem Based Learning (PBL) untuk Meningkatkan Hasil Pembelajaran Tematik Terpadu di Sekolah Dasar - Hamidah, Nur Hidayatul; Nasrul, Nasrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research is motivated by the low of student learning outcomes in class IV SD Negeri 09 Belakang Balok Bukittinggi.This study aim to describe the improvement of student learning outcomes on integrated thematic learning by applying Problem Based Learning model in the fourth grade students SD Negeri 09 Belakang Balok Kota Bukittingg . Type of research is PTK by using qualitative and quantitative approach. The result of student learning cycle I 72,62 increased to 88,83 in cycle II. The conclusion is applying Problem Based Learning model can improve the learning outcomes of integrated thematic learning in elementary school.